Long-term effectiveness of a nurse-led 7-step transitional intervention programme in heart failure. (25th November 2020) - Alcoberro, L; Vime, J; Enjuanes, C; Jimenez, S; Garay, A; Yun, S; Moliner, P; Guerrero, C; Hidalgo, C; Calero, E; Marin, R; Alcober, L; et al.
Abstract: Background: Reduction of 30-day readmission in heart failure (HF) patients is a main goal of health-care systems. Programmes to decrease 30-day readmission have successfully reduced it but have failed to neither maintain benefit afterwards nor decrease mortality. Moreover, in many cases the price of reducing 30-day readmission is a mortality increase. Purpose: Evaluate whether the impact of a fully nurse-led HF programme directed to reduce 30-day readmission and mortality extends to longer periods of time, including 90 days and 180 days after discharge. Methods: We evaluated all patients discharged from hospital with HF as primary diagnosis between January 2017 and January 2019. We compared outcomes between patients discharged during Period #1 (pre-programme; Jan 2017 - Aug 2017) and those discharged during Period #2 (HF programme; Sept 2017 - Jan 2019). Primary endpoint was the combined endpoint of all-cause death or all-cause hospitalization 90 days and 180 days after discharge from the index hospitalization. Results: The study enrolled 440 patients: 123 in Period #1 and 317 in Period #2. Mean age was 75±9 years. There was a higher proportion of female patients in Period #2 (38.2% vs 26.8%, p=0.025), with no differences in other baseline characteristics. The combined endpoint of all cause-death and all-cause hospitalization was significantly reduced in patients in the HF programme group, both at 90 days [OR 0.37 (0.22–0.63), p<0.001] and at 180 days [OR 0.27 (CI 0.17–0.43), p<0.001]. Such a decrease was at expense of a reduction in cardiovascular (CV) hospitalization and HF hospitalization. There were no differences between groups in mortality [OR 0.96 (0.18–5.00), p=0.293]. Conclusions: A fully nurse-led HF programme reduces the combined endpoint of all-cause death and all-cause hospitalization both at 90 days and 180 days after an index discharge for HF. Such a decrease is driven by a reduction of CV and HF hospitalization, which are maintained over time. There were no differences between groups in mortality. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Hospital Universitari de Bellvitge